Implementasi SSL untuk Keamanan Data pada Sistem Inventaris - Mufreni, Sadr Lufti; Wijayanto, Danur; Maryani, Sri (Faculty of Computer Science, University of Jember, 2024)
The issue of data security and confidentiality of communications on the network is one of the most important aspects. Data security in the Inventory System is currently not completely safe; this is because the Inventory System has not implemented client and server communication security. Secure Socket Layer (SSL) is one of the efforts that can be made to prevent illegal attacks. This study applied the SSL method, in which SSL acted as a data security protocol in client and server communication networks. The purpose of this research was to implement SSL in order to improve data security in the Inventory System at Sanggar Tari Natya Lakshita. The process of observing and analyzing the data security of the Inventory System was carried out using Wireshark tools. The results showed that the implementation of SSL in the Inventory System was successful; this was evidenced by the results of observing and analyzing the data packets captured by Wireshark; the data was not easy to read. The success rate of doing 3 trials, namely logging in, inputting and deleting the data packet, was 100% encrypted.